The Experiences of Strategic Purchasing of Healthcare in Nine Middle-Income Countries: A Systematic Qualitative Review - Joshua Sumankuuro; Frances Griffiths; Adam D. Koon; Witness Mapanga; Beryl Maritim; Atiya Mosam; Jane Goudge (International Journal of Health Policy and Management, 2023)
Background  Efforts to move towards universal health coverage (UHC) aim to rebalance health financing in ways that increase efficiency, equity, and quality. Resource constraints require a shift from passive to strategic purchasing (SP). In this paper, we report on the experiences of SP in public sector health insurance schemes in nine middle-income countries to understand what extent SP has been established, the challenges and facilitators, and how it is helping countries achieve their UHC goals.Methods  We conducted a systematic search to identify papers on SP. Nine countries were selected for case study analysis. We extracted data from 129 articles. We used a common framework to compare the purchasing arrangements and key features in the different schemes. The evidence was synthesised qualitatively.Results  Five countries had health technology assessment (HTA) units to research what services to buy. Most schemes had reimbursement mechanisms that enabled some degree of cost control. However, we found evidenced-based changes to the reimbursement mechanisms only in Thailand and China. All countries have some form of mechanism for accreditation of health facilities, although there was considerable variation in what is done. All countries had some strategy for monitoring claims, but they vary in complexity and the extent of implementation; three countries have implemented e-claim processing enabling a greater level of monitoring. Only four countries had independent governance structures to provide oversight. We found delayed reimbursement (six countries), failure to provide services in the benefits package (four countries), and high out-of-pocket (OOP) payments in all countries except Thailand and Indonesia, suggesting the schemes were failing their members.Conclusion  We recommend investment in purchaser and research capacity and a focus on strong governance, including regular engagement between the purchaser, provider and citizens, to build trusting relationships to leverage the potential of SP more fully, and expand financial protection and progress towards UHC.